Penile Sclerosing Lipogranuloma : A Case Report - Baginda Pascal Agung Hamonangan Manik; Arley Sadra Telussa (Universitas Nusa Cendana, 2026)
Background: penile injection with foreign materials mainly done by non-medical personnel with the aim to enlarge penis size. Complications occur by this injection of foreign materials called Penile Sclerosing Lipogranuloma. Case illustration: A 22-year-old male came presented with main complain of multiple masses in his penis. Previous history of disease also denied by the patient. Patient said that 4 years ago, he underwent a penile enlargement injection in his penile shaft. This injection performed by non-medical personnel. In physical examination, multiple large masses palpable almost along the penile shaft, masses were firm on palpation. A wide excision on the damaged skin was performed and scrotal flap was used to cover the exposed area in the penile shaft. Discussion: we performed wide excision followed by scrotal flap to cover the exposed area. We considered this technique is suitable for this patient because the scrotal skin is healthy and enough to cover the exposed area on penile shaft. Conclusion: Surgical treatment is considered the best treatment to treat Penile Sclerosing Lipogranuloma. Surgical treatment aimed to remove the damaged skin part and fibrotic tissue caused by foreign material.